RELATIONSHIP BETWEEN SELF DISCLOSURE AND LONELINESS AMONG HIGH SCHOOL STUDENTS WHO USE THE SOCIAL MEDIA PLATFORM INSTAGRAM IN BATUSANGKAR - Zahra, Adifa; Primanita, Rida Yanna (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This study aims to determine the relationship between self-disclosure and loneliness in high school students who use Instagram in Batusangkar. The study used a correlational quantitative approach with 105 respondents selected through purposive sampling technique. The instruments used are self-disclosure and loneliness scales. The Spearman test results showed a positive and significant relationship between self-disclosure and loneliness (r = 0.598; p < 0.05). The higher the self-disclosure, the higher the level of loneliness felt. Self-disclosure contributed 35% to loneliness. These results support previous research and show the importance of self-disclosure in building healthy social relationships.